2016
DOI: 10.3126/banko.v26i1.15496
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the environment on species richness and composition of vascular plants in Manaslu Conservation Area and Sagarmatha region of Nepalese Himalaya

Abstract: This study analyzed how the environmental conditions constrained the species richness and composition in the four river valleys of Central Nepal i.e. two from Manaslu Conservation Area (MCA) and two from Sagarmatha region. Topographical, bioclimatic and measured variables were used to analyze their effects on the vascular plant diversity along elevation and land use gradients. Altogether, 148 plots were established at five elevation levels between 2,200 m and 3,800 m above the mean sea level. Four land use typ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 43 publications
(68 reference statements)
1
6
0
Order By: Relevance
“…Therefore, isothermality plays a vital role in the biodiversity and ecology of a region. Rai et al ( 2016 ) reported the most significant effect of TBI3 on the plant composition among all the indicators. Sommer et al ( 2010 ) estimated a reduction of biological diversity with an increase in temperature.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, isothermality plays a vital role in the biodiversity and ecology of a region. Rai et al ( 2016 ) reported the most significant effect of TBI3 on the plant composition among all the indicators. Sommer et al ( 2010 ) estimated a reduction of biological diversity with an increase in temperature.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, isothermality plays a vital role in the biodiversity and ecology of a region. Rai et al (2016) reported the most significant effect of TBI3 on the plant composition among all the indicators. Sommer et al (2010) estimated a reduction of biological diversity with an increase in temperature.…”
Section: Isothermality (Tbi3)mentioning
confidence: 98%
“…In each valley, five elevation bands were selected at different locations (around 2200, 2400, 2800, 3200, 3800 m a.s.l.) (Scheidegger et al 2010;Katuwal et al 2016;Rai et al 2016). At the "local level" (i.e.…”
Section: Field Work and Species Datamentioning
confidence: 99%